Unplanned Development : Tracking Change in South-East Asia. - Rigg, Jonathan (Zed Books, 2012)
Unplanned Development offers a fascinating and fresh view of development planning. While to the outsider most development projects present themselves as thoroughly planned endeavours, informed by structure, direction and intent, Jonathan Rigg exposes the reality? that chance, serendipity and turbulence define development around the world. Based on rich empirical research in South-East Asia, Unplanned Development asks vital questions on the underlying paradoxes of development practice.